Occupational exposures to formaldehyde and wood dust in nasopharyngeal carcinoma: A 10-year case series from Tunisia - Athimni, Zeineb; Aloui, Asma; Maoua, Maher; Kacem, Imen; Makhlouffi, Manel; Bouhoula, Marwa; Chouchene, Asma; Brahem, Aicha; Kalboussi, Houda; EL Maalel, Olfa; Chatti, Souheil (Biomedicine & Healthcare Research, 2025)
Introduction: Nasopharyngeal cancer is a distinctive entity compared to other head and neck cancers. In Tunisia, it is ranked as the second most common head and neck cancer after laryngeal cancer. Although its pathophysiology is unclear, several genetic and infectious predisposing factors have been identified. However, there is limited data available on environmental and occupational factors. Material and method: This is a retrospective descriptive survey of the records of subjects with nasopharyngeal cancer. These subjects consulted the occupational medicine department of the Farhat Hached University Hospital, Sousse, over a 10-year period from 1 January 2010 to 31 December 2019. Results: A total of four cases were recorded, illustrating a variety of occupational exposures. All patients were males. Cervical adenopathy was the first symptom to appear. The diagnosis was confirmed by biopsy. Pathological examination revealed 3 undifferentiated nasopharyngeal carcinoma (UCNT) and one well-differentiated non-keratinizing squamous cell carcinoma. Two patients were welders, one was a qualified dairy production operator and the fourth was a worker in a car company. Three patients were exposed to formaldehyde and one to wood dust with an average seniority of 11.25 years. All four cases had their cancer recognized as an occupational disease according to table 28 or 54. Conclusion: All cases of nasopharyngeal cancer should be considered to be of work-related origins, so that it can be recognized as an occupational disease and so that patients' rights to treatment and compensation can be preserved.